Financial regulation and reform : the theoretical basis, lessons from experience and appropriate strategies for Caribbean policy-makers. - SEERATTAN, Dave Arnold (1995)
Outlines the type, rationale and objective of financial reform, and presents the theoretical rationale for these reforms. Looks at the effect of financial reform on innovations and the development of financial services, and reviews some recent developments in the financial sectors of caribbean countries.